PERSEPSI GURU TERHADAP PENGARUH DONGENG PADA OTAK ANAK USIA DINI - Regina Farhani; Silvi Ananda Suwandi; Shelvira Amanda Putri; Masyunita Siregar (Al-Abyadh, 2023)
The rapid development of information technology, marked by the rise of national private television broadcasts, games, the internet and other entertainment media, is increasingly capturing the attention of the public, especially children. Storytelling activities that used to be often heard are now rarely done by parents or other parties to children. The purpose of this study was to determine the teacher's perception of the influence of fairy tales on children's brains. The research design used is a survey research method with a quantitative approach (Quantitative Research). Data was collected through a questionnaire to twenty early childhood teachers. After the data was collected, the researchers analyzed the data using quantitative data analysis techniques. From the results of the data analysis, the researcher could conclude that fairy tales have an effect on early childhood brain development because fairy tales have many positive impacts on children, including fairy tales can improve children's brain performance, grow creativity. and children's imagination, strengthen social and family bonds, improve communication, can train children's sense of empathy and awareness. through fairy tales can also teach ancestral values ​​including tolerance. Besides being very popular with children, through fairy tales educators can provide various advice, advice, examples, or wisdom through the characters of a story.